Morfologia externa comparada das três espécies do complexo Telchin licus (Drury) (Lepidoptera, Castniidae) com uma sinonímia Comparative external morphology of the three species of the Telchin licus (Drury) complex (Lepidoptera, Castniidae) with a synonymy - Simeão S. Moraes; Marcelo Duarte (Revista Brasileira de Entomologia, 2009)
É apresentado um estudo morfológico detalhado da cabeça, do tórax e do abdome de três espécies próximas de castníideos neotropicais. O posicionamento taxonômico dessas espécies é ainda bastante controverso. Antes do desenvolvimento do presente estudo, duas dessas espécies pertenciam ao gênero Telchin Hübner, 1825 e uma ao gênero monotípico Castniomera Houlbert, 1918 (espécie-tipo: Castnia atymnius Dalman, 1824). A hipótese de alguns autores de incluir as três espécies do complexo T. licus em um único gênero é aqui sustentada com base em evidências morfológicas de cabeça, tórax e abdome. Castniomera Houlbert torna-se sinônimo de Telchin Hübner compreendendo as seguintes espécies: Telchin licus (Drury, 1773), Telchin syphax (Fabricius, 1775) e Telchin atymnius (Dalman) combinação nova. As três espécies do complexo T. licus são ilustradas com desenhos e fotografias coloridas. A detailed morphological study of head, thorax, and abdomen is provided for three closely related species of Neotropical sun-moths. The taxonomic position of these species is controversial. Prior to the present study two of these species belonged to the genus Telchin Hübner, 1825, and one to the monotypic genus Castniomera Houlbert, 1918 (type species: Castnia atymnius Dalman, 1824). The hypothesis of some authors of placing the three species in a single genus is here supported on morphological evidences from head, thorax, and abdomen. Castniomera Houlbert is treated as synonym of Telchin Hübner comprising the following species: Telchin licus (Drury, 1773), Telchin syphax (Fabricius, 1775), and Telchin atymnius (Dalman) new combination. The three species of the T. licus complex are illustrated with line drawings and color photographs.